The Effect of Job Stress and Perceived Organizational Sup-port on Employee Performance at PT. Canova Semarang (Pusat Riset dan Inovasi Nasional, 2026)
The high operational demands in the production logistics division of PT. Canova Semarang are a crucial issue because they have the potential to trigger job stress that can affect employee stability and productivity, while perceived organizational support is seen as an organizational factor that can strengthen performance. Theoretically, this study is based on the theory of work stress and social exchange theory which explain that performance is influenced by psychological factors and institutional support. This study aims to analyze the effect of Job Stress and Perceived Organizational Support on Employee Performance with a quantitative approach using saturated sampling techniques on 65 employees and multiple linear regression analysis. The results show that job stress has a significant effect on performance, where managed stress can improve performance but excessive stress decreases work quality, while Perceived Organizational Support has a positive and significant effect on performance. These findings emphasize the importance of proportional stress management and strengthening organizational support to maintain sustainable employee productivity.